Kajian Struktural Hikayat Iskandar Zulkarnain Episode Islamisasi Habsyi - Uli, Indriyana (Universitas Hamzanwadi, 2018)
This study aims to describe the intrinsic structure of Hikayat Iskandar Zulkarnain episode of IslamisasiHabsyi. The form of this research is descriptive qualitative. The approach used is a structural approach. Theresults showed intrinsic structure of theme, plot, characterization, background, and mandate. The structureprovides an overview of the story of a most prominent Islamic hero explaining the principles of Islam to his newadherents. The plot is using forward flow. With the main character named Iskandar is a great king. Thebackground of storytelling has a name and only certain initials, among others, the country of Andalas and the socalledant quartet. The message in Hikayat is humble in spite of Iskandar Zulkarnaen's glorious triumph